Infrapolitical resistance to management control in the home workplace - Chelli, Mohamed; Himick, Darlene (Accounting, Organizations and Society, 2026)
In this study, we examine how workers resist management controls in the home workplace. Drawing on Scott's (1985, 1990) theorization about the everyday forms of resistance, especially his seminal concepts of infrapolitical resistance and hidden transcripts, and mobilizing a netnographic approach, we examine the comments posted on Reddit during a 10-month period, in which workers talk about their resistance to the ways in which they are controlled in the home-based work environment. We uncover six hidden transcripts representing workers' infrapolitical resistance to management control in the home workplace, which we categorize into two sets: resistance thoughts and beliefs and individual acts of resistance. Home office workers describe and discuss their resistance attitudes and ideas around 1) the new limits of acceptable levels and types of controls, 2) the very worth of the managerial role, and 3) employers' cultural controls. Also, home office workers resist via their actions by 4) performing “empty labor; ” 5) quitting their job in response to return-to-office mandates; and 6) selectively meeting productivity-related controls. Bringing a new empirical site − the home as a workplace − to the management control literature, we theorize about the ways in which home office workers transform productivity into a site of resistance, turn the control gaze back on the managers, and use the home office to resist controls.